A Gradientless Reactor for Kinetic Studies of Catalytic Processes - D. Nazimek; J. Ryczkowski (Adsorption Science & Technology)
The gradientless technique for determining the rate of catalytic reaction has more or less replaced other traditional methods for longer time studies. To determine the reaction rate, rotating reactors in which the catalysts are placed are most frequently used, as well as stirred gas reactors where the catalyst is stationary. The present paper reports on the construction of a gradientless reactor for kinetic studies of catalytic processes at high temperatures.